ชุมชนกับการธำรงรักษาฐานประชาธิปไตยชุมชน : กรณีศึกษาชุมชนควนรู อำเภอรัตภูมิ จังหวัดสงขลา - ชัยวัฒน์ โยธี (มหาวิทยาลัยสงขลานครินทร์ วิทยาเขตปัตตานี, 2024)
This study_ aims to study_ the development of community democracy in order to identify factors that hinder the preservation of the community democratic base of the Quan Ru community. This includes finding models or approaches*to developing local government using community-based democracy. qualitative research methods have been used by taking community lessons, in-depth interviews, and group discussions which include participatory and non-participatory observations The study found that the development of community democracy in the Quan Ru community. There are 4 things that can be demonstrated: 1) base formation consisting of being born by way of life and being born by state policy, 2) the development of the people's sector consisting of political management within the community, the discovery of community development guidelines and adaptation of the community 3) Expanding the community democracy base consists of using a community master plan and using community organizations as tools for success 4) Organization fusion as coordination of 3 organizations. locality, locality, locality, etc. The factors that hinder the preservation of the community democracy base of the Quan Rou community are factors within the community, namely: 1) individuals and leaders, 2) groups - organizations, consisting of The national gross economy. rapidly changing social structures affecting people's beliefs, the threat of COVID-19, social and cultural and religious aspects 3) the institutional aspects of governance are the disruption of local government mechanisms and the threat of national political mechanisms 4) social, cultural and religious factors, resulting in fewer people gathering in religious activities. External factors are: 1) Political is a national political phenomenon that changes and affects local government and the whole system structure 2) Economic aspects caused by government policies affecting local communities, especially agricultural policies, 3) Social and cultural aspects, which are rapid changes in the world that affect social structures at all levels, 4) The threat of COVID-19 has disrupted the community society in all dimensions, The model or approach to the development of local government using community democracy as a base is divided into 2 main areas of development: personnel development, followed by organizational development, which is developed in 3 levels: 1. Building a base of thought, 2. Level of development of individual potential, 3. The main focus of community affairs operations is on people's participation and critical consultation and integration